2017
DOI: 10.1024/0300-9831/a000444
|View full text |Cite
|
Sign up to set email alerts
|

Increased vitamin B12 levels in children with zinc deficiency

Abstract: Additional nutritional deficiencies may accompany zinc deficiency. We determined the vitamin B levels in patients with zinc (Zn) deficiency. This retrospective study enrolled 256 patients age 6 months to 16 years (176 females and 80 males) in whom Zn levels in hair samples were measured concurrently with serum vitamin B and ferritin levels. For all patients, we retrospectively assessed the hair Zn levels, serum ferritin and vitamin B levels, red blood cell count, hemoglobin, hematocrit, mean corpuscular volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In contrast to the results of our study, Betul Ergul et al, the study showed that in the zinc-deficient group, vitamin B12 level was significantly higher than in the normal group (19). It can be inferred that these discrepancies might be due to individual differences and variant dieting patterns among different populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of our study, Betul Ergul et al, the study showed that in the zinc-deficient group, vitamin B12 level was significantly higher than in the normal group (19). It can be inferred that these discrepancies might be due to individual differences and variant dieting patterns among different populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Zinc deficiency is considered a very serious health problem since it is the fifth most important cause of disease, leading to morbidity and mortality (11)(12)(13). Many studies have shown that zinc deficiency in humans causes postponed growth, skin lesions, and sexual dysfunction in adolescents (16)(17)(18)(19). The need for zinc in childhood is crucial because of rapid growth, the main characteristic of this age span.…”
Section: Introductionmentioning
confidence: 99%